Father’s Involvement in Parenting as a Predictor of Adolescents' Social Adaptation - Nadia Miranti Kusumasari (Psychological Research and Intervention, 2020)
The purpose of this study is to determine the effect of father's involvement towards social adjustment in adolescent. This study uses quantitative approaches with the type of survey research. The population of this study are 437 students of 7th and 8th grade at MTs A Yogyakarta with 211 students as a sample which determined by simple random sampling technique. Data was collected by using father’s involvement scale and social adjustment scale. Validity in the scale of this study used content validity carried out by expert. Reliability in the scale of this study used Alpha Cronbach reliability coefficient of 0,951 on the father’s involvement scale and 0,905 on the social adjustment scale. As for data analysis, descriptive analysis and simple linear regression analysis are used. The results of this study showed that father’s involvement has a significant contributed 27,1% towards social adjustment in adolescent (F = 77,672; p = 0,000 α 0.05). As for the line of regression equation obtained is Y = 47,789 + 0,289X.